2022
DOI: 10.1177/02724316221088750
|View full text |Cite
|
Sign up to set email alerts
|

Shyness, Unsociability, and Social Avoidance During Early Adolescence: Associations With Peer Relationships and Aggression

Abstract: We investigated how 5th–8th graders’ self- and peer-identified withdrawal motivations predicted peer-reported peer relationships and aggression. Participants ( N = 221; 47% male) provided self-reports and peer-nomination data (we analyzed 339 students’ nominations). We hypothesized shyness, unsociability, and avoidance would predict low peer liking and high exclusion; shyness and avoidance would predict high victimization and peer disliking; and avoidance would predict high aggression. Support was mixed. Resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 41 publications
(120 reference statements)
0
8
0
Order By: Relevance
“…Social avoidance is considered an extreme form of shyness/social anxiety and represents an early manifestation of depression ( Asendorpf, 1990 ; Schmidt and Fox, 1999 ). Consistent with this assertion, results from several studies found social avoidance is associated with maladjustment outcomes, such as peer exclusion, loneliness, and depression in Western societies ( Bowker et al, 2017 ; Coplan et al, 2018 , 2021 ; Eggum et al, 2022 ; Sette et al, 2022 ). For example, Sette et al (2022) found that, after controlling for shyness and unsociability, social avoidance was positively associated with loneliness, regardless of children’s age or gender, in Italian children.…”
Section: Overview Of Social Avoidance In Childhoodmentioning
confidence: 55%
See 4 more Smart Citations
“…Social avoidance is considered an extreme form of shyness/social anxiety and represents an early manifestation of depression ( Asendorpf, 1990 ; Schmidt and Fox, 1999 ). Consistent with this assertion, results from several studies found social avoidance is associated with maladjustment outcomes, such as peer exclusion, loneliness, and depression in Western societies ( Bowker et al, 2017 ; Coplan et al, 2018 , 2021 ; Eggum et al, 2022 ; Sette et al, 2022 ). For example, Sette et al (2022) found that, after controlling for shyness and unsociability, social avoidance was positively associated with loneliness, regardless of children’s age or gender, in Italian children.…”
Section: Overview Of Social Avoidance In Childhoodmentioning
confidence: 55%
“…The “functioning” of social behavior is determined by social and cultural contexts ( Chen and French, 2008 ). For social withdrawal, especially shyness and unsociability, previous studies mainly focused on Western and urban Chinese children ( Liu et al, 2015 ; Coplan et al, 2018 ; Ding et al, 2019 ; Poole et al, 2020 ; Eggum et al, 2022 ; Sette et al, 2022 ). To expand the research in this area, the present study examined the relations between social avoidance and socio-emotional functioning, and further explored the moderating role of marital conflict in the links between social avoidance and indices of socio-emotional functioning among young children in the context of contemporary suburban China.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations